VIRTUAL REALITY-BASED MEDIA TO ENHANCE SUNDANESE DESCRIPTIVE WRITING SKILLS - Anjani Ridho; Usep Kuswari; Haris Santosa Nugraha (Universitas Majalengka, 2025)
Learning to write Sundanese descriptive texts presents several challenges, particularly in the limited availability of engaging and contextualized learning media. Students often lack real-life experiences related to the objects they are asked to describe, and the absence of interactive media contributes to the low quality of their descriptive writing. This study aims to analyze the needs for Virtual Reality media to enhance students’ skills in writing Sundanese descriptive texts at the junior high school level. A descriptive qualitative method was employed in this research. The participants included 8 Sundanese language teachers and 145 junior high school students from Bandung City. Data were collected through questionnaires and interviews conducted during the 2024/2025 academic year. The collected data were analyzed using qualitative techniques involving data reduction, data display, and conclusion drawing. The results indicate that students’ ability to write Sundanese descriptive texts remains relatively low, primarily due to the lack of innovative and immersive learning media. Teachers also face challenges in providing learning experiences that allow students to observe or visualize descriptive objects directly. Virtual Reality shows potential as a promising solution, offering immersive, simulated environments that help students gain contextual understanding. These findings suggest that the development of Virtual Reality media is urgently needed to support students’ learning needs in writing Sundanese descriptive texts. Furthermore, this study serves as a foundation for future research focusing on the design and effectiveness of Virtual Reality-based learning media in enhancing descriptive writing skills in Sundanese language education.